2015
DOI: 10.1002/ajmg.a.36917
|View full text |Cite
|
Sign up to set email alerts
|

Is cardiac rhabdomyoma a feature of Birt Hogg Dubé syndrome?

Abstract: We report on a child with two cardiac rhabdomyomas. Initially, a diagnosis of Tuberous Sclerosis Complex (TSC) syndrome was suspected, although this could neither be confirmed clinically nor genetically. Coincidentally, Birt Hogg Dubé syndrome (BHD) had been previously diagnosed in members of the extended family; this prompted a diagnostic re-evaluation of the child who was found to have the known family FLCN mutation. We recommend consideration of cardiac rhabdomyomas as part of the clinical BHD spectrum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…There have been two reported cases of cardiac rhabdomyoma [Toro et al, ; Bondavalli et al, ] in BHD, and a report of fibrofolliuculoma, characteristic of BHD, within a cluster of angiofibromas in an individual with TSC [Misago and Narisawa, ]. Additionally, two prior reports of renal AML in patients with BHD support the emerging evidence of a phenotypic overlap between the two syndromes [Byrne et al, ; Tobino and Seyama, ].…”
Section: Discussionmentioning
confidence: 93%
“…There have been two reported cases of cardiac rhabdomyoma [Toro et al, ; Bondavalli et al, ] in BHD, and a report of fibrofolliuculoma, characteristic of BHD, within a cluster of angiofibromas in an individual with TSC [Misago and Narisawa, ]. Additionally, two prior reports of renal AML in patients with BHD support the emerging evidence of a phenotypic overlap between the two syndromes [Byrne et al, ; Tobino and Seyama, ].…”
Section: Discussionmentioning
confidence: 93%
“…FNIP1 interacts with 5′AMP-activated protein kinase (AMPK), a key molecule for energy sensing that negatively regulates mTOR activity, suggesting that FLCN may be regulated by mTOR and AMPK signaling [1, 17]. This has lead Bondavalli et al to raise the possibility that mutations in FLCN might be the cause of cardiac rhabdomyomas and argue for BHD to be included in the differential diagnosis of these hamartomas [5].…”
Section: Discussionmentioning
confidence: 99%
“…A single ‘rhabdomyoma’ has been described among the cohort of 51 families with BHD syndrome, but its site was not indicated [4]. Since then, an adult rhabdomyoma in a presumed parathyroid adenoma and a cardiac rhabdomyoma in an infant carrying a FLCN mutation have been described [5]. We report an adult laryngeal rhabdomyoma in a patient with BHD syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…The CDC's detailed data on 27 cases of MIS-A included two cases with deranged inflammatory markers, ECG and TTE changes, which recovered on only anticoagulants without IVIg or steroids. 1 Hence, there might be a subset of patients with K-MIS-A who may recover spontaneously without conventional therapies. The focus of our case is to reiterate the possibility of COVID-19-associated K-MIS-A and timely diagnosis through early identification of dermatological manifestations and antibody testing, even when COVID-19 RT-PCR is negative.…”
mentioning
confidence: 99%
“…This variant segregated with the BHD phenotype in this family and has been reported in several prior BHD syndrome pedigrees. 1 One affected brother had a history of unilateral human papillomavirus-positive tonsillar squamous cell carcinoma, which had metastasized to the lymph nodes. Ultrasound and computed tomography studies of the head and neck in the proband demonstrated three homogeneous soft-tissue masses within the left submandibular and bilateral sublingual spaces (Figure 1b).…”
mentioning
confidence: 99%